Whakawhanaungatanga: the importance of culturally meaningful connections to improve uptake of pulmonary rehabilitation by Māori with COPD – a qualitative study - Levack WMM; Jones B; Grainger R; Bol; P; Brown M; Ingham TR (International Journal of COPD, 2016)
William MM Levack, Bernadette Jones, Rebecca Grainger, Pauline Boland, Melanie Brown, Tristram R Ingham Department of Medicine, University of Otago, Wellington, New Zealand Background: Pulmonary rehabilitation is known to improve function and quality of life for people with chronic obstructive pulmonary disease (COPD). However, little research has been conducted on the influence of culture on experiences of pulmonary rehabilitation. This study examined factors influencing uptake of pulmonary rehabilitation by Māori with COPD in New Zealand. Method: Grounded theory nested within kaupapa Māori methodology. Transcripts were analyzed from interviews and focus groups with 15 Māori and ten New Zealand non-Māori invited to attend pulmonary rehabilitation for COPD. Māori participants had either attended a mainstream hospital-based program, a community-based program designed “by Māori, for Māori”, or had experienced both. Results: Several factors influencing uptake of pulmonary rehabilitation were common to all participants regardless of ethnicity: 1) participants’ past experiences (eg, of exercise; of health care systems), 2) attitudes and expectations, 3) access issues (eg, time, transport, and conflicting responsibilities), and 4) initial program experiences. These factors were moderated by the involvement of family and peers, interactions with health professionals, the way information on programs was presented, and by new illness events. For Māori, however, several additional factors were also identified relating to cultural experiences of pulmonary rehabilitation. In particular, Māori participants placed high value on whakawhanaungatanga: the making of culturally meaningful connections with others. Culturally appropriate communication and relationship building was deemed so important by some Māori participants that when it was absent, they felt strongly discouraged to attend pulmonary rehabilitation. Only the more holistic services offered a program in which they felt culturally safe and to which they were willing to return for ongoing rehabilitation. Conclusion: Lack of attention to cultural factors in the delivery of pulmonary rehabilitation may be a barrier to its uptake by indigenous, minority ethnic groups, such as New Zealand Māori. Indigenous-led or culturally responsive health care interventions for COPD may provide a solution to this issue. Keywords: COPD, pulmonary rehabilitation, health care access, cultural safety, indigenous peoples, qualitative research